Perlindungan Hukum terhadap Konsumen Produk Makanan yang Tidak Berlabel Halal di Daerah Istimewa Yogyakarta Tahun 2015 - Umdah Aulia Rohmah; Iswantoro Iswantoro (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2016)
The results showed that the majority of manufacturers micro and kecildi Special RegionYogyakartabelum have a halal certificate, some others even labeled halal themselves without acertificate of kosher and halal label does not list an official of BPJPH (Halal Product SecurityAgency). Efforts legal protection of the consumer by the government in food products that are notlabeled halal is to set up surveillance guarantees halal products, the issuance of an Act to regulate thecertification and labeling of halal, socializing, appeals or withdrawal of products that violate theprovisions of halal labeling, the establishment of the agency organizing halal product assurance, theestablishment of halal audit institution, formed auditor kosher, halal label the presence of officialand criminal sanctions for violating the provisions stipulated in the Act. Obstacles faced by foodmanufacturers in labeled halal is halal labels mandatory, but only a small part for businesses whoare conscious about the importance of label kosher, halal certification process complicated, difficult,cost factors and conditions and process that takes time old makes businesses reluctant to take care ofit. It is suggested to producers or businesses to pay attention to consumer rights. to consumers to bemore careful in buying food that is not labeled halal, to the government to seriously address the issueof halal labeling so that consumers' rights guaranteed.